An Overview of Total Medical Information Systems - BALL, M. J. (Methods of Information in Medicine, 1971)
This paper is addressed to the practising physician, hospital administrator, and allied health professional. The function of a computerized information system in health care today is defined as a traffic controller, Factors justifying the implementation of a hospital information system will be discussed and the crucial considerations of competent management and long-range education explained. The paper describes various philosophies undertaken and reviews the approaches of a sampling of vendors and organizations endeavoring to implement computerized hospital information systems. Included in each system discussion is: 1.) a brief description of the functions undertaken, 2.) hardware and software used, type of terminal used for input at designated stations, 3.) a listing, where possible, of planned and/or present instillations, 4.) an approximate cost figure, where available, and 5.) a brief statement containing additional information.The Appendix composes a list of locations of operational total systems should the reader desire either to arrange a site visit or obtain additional information.
Keywords: Total Medical Information Systems; Computerized Patient Care; Hospital Information System (HIS); Control of Hospital Functions; System Philosophies; Advantages of HIS; Cost Justification